Slight ligand modifications within multitopic linear hydroxamates promotes connectivity differences in Cu(ii) 1-D coordination polymers - Mohammed B. Fugu; Joe Coley; Isabella F. Dickinson; James B. Orton; Wim T. Klooster; M. Paul Gleeson; Leigh F. Jones (CrystEngComm, 2021)
Two novel hydroxamic acids have been used in constructing two 1-D coordination polymers. Slight structural differences promote connectivity changes upon Cu( ii ) metalation as rationalised using DFT calculations and Hirschfeld surface analysis.
Keywords: Metal-Organic Frameworks: Synthesis and Applications; Magnetism in coordination complexes; Crystallography and molecular interactions